ADP-ribosyltransferase from Helix pomatia. Purification and characterization. - Burtscher, H J (1987)
ADP-ribosyltransferases from several higher eukaryotes have been purified and characterized, but little is known about ADP-ribosyltransferases in lower eukaryotes. We have purified an ADP-ribosyltransferase (EC 2.4.2.30) from Helix pomatia. The enzyme has an apparent Km of 26.7 microM. Optimal conditions for the enzyme reaction are 17.5 degrees C and pH 8. The time course is linear during the first 10 min of the reaction. The enzyme is capable of poly-ADP-ribosylation. The most highly purified preparation shows one major band at an Mr of 75,000 on electrophoresis in an SDS/polyacrylamide gel, with minor bands at Mr 115,000 and 155,000. Re-activation of SDS/polyacrylamide gels in situ shows the 75,000-Mr band to be enzymically active and additional active bands with Mr values of 115,000, 90,000 and 87,000 respectively. The 115,000-Mr and 75,000-Mr bands cross-react with a polyclonal affinity-purified antiserum against human ADP-ribosyltransferase. Like enzymes from higher eukaryotes, the activity from Helix pomatia is inhibited by thymidine, theophylline, theobromine nicotinamide, 3-methoxybenzamide and 3-aminobenzamide, and is dependent on histone and DNA.